How outsourcing HR created a profitable scenario for Nestle and PeopleScape Ltd? - Bhattacharjee, Arpita (BRAC University, 2013)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2012.